2010
DOI: 10.1007/s10964-010-9588-4
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Relationships Between Rural Adolescents’ Prosocial Behaviors and Young Adult Substance Use

Abstract: While many adolescents and young adults experiment with substances (e.g., alcohol, cigarette smoking, marijuana), recent research suggests that rural youth and young adults may be more at risk for substance use than their urban counterparts. This study was designed to examine the longitudinal relationships between rural adolescents' prosocial behaviors and substance use in young adulthood. Furthermore, we examined the potential mediating effects of adolescent substance use, academic investment, and delinquency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 42 publications
4
48
0
2
Order By: Relevance
“…In fact, a case could be made that the causal direction is the reverse: that is, that these more favourable social circumstances nurture prosocial behaviour. Nevertheless, our data are very much in line with previous research with typical populations in studies which do point to protective effects (Carlo, Crockett, Wilkinson, & Beal, 2011; Cillessen et al, 2005; Markiewcz et al, 2001). …”
Section: Discussionsupporting
confidence: 92%
“…In fact, a case could be made that the causal direction is the reverse: that is, that these more favourable social circumstances nurture prosocial behaviour. Nevertheless, our data are very much in line with previous research with typical populations in studies which do point to protective effects (Carlo, Crockett, Wilkinson, & Beal, 2011; Cillessen et al, 2005; Markiewcz et al, 2001). …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of a recent longitudinal study, in which adolescents with high levels of academic investment (e.g., participation in academic activities, academic plans, perceived importance of school, grades, and how much they liked school) in tenth to twelfth grades had less substance use (getting drunk, cigarette use, and marijuana) seven years later than did those with relatively low levels of academic investment in high school (Carlo, Crockett, Wilkinson, & Beal, 2011). In contrast to other studies of cognitions focused only on a single domain of alcohol use (e.g., alcohol expectancies, drinker prototype, or intention to drink), we found that self-cognitions in other domains, particular in academics, are protective against alcohol consumption in adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Difficulties with peers have, for example, been shown to place children at risk for later externalizing, internalizing and school problems (Rubin, Bukowski, & Parker, 2006). In contrast, prosocial behavior is associated with academic success and positive peer relationships (Caprara, Barbaranelli, Pastorelli, Bandura, & Zimbardo, 2000), low levels of externalizing problems (Eisenberg, Fabes, & Spinrad, 2006) and fewer health-risk behaviors in adulthood (Carlo, Crockett, Wilkinson, & Beal, 2011). …”
Section: Discussionmentioning
confidence: 99%